The Potential Uses and Missuses of AI-Powered Writing Skills on Academic Writing: Students' Side - Dangin Dangin; Isti’anatul Hikmah (Journal on Education, 2024)
Recently, the use of AI-powered writing tools has become so popular among different academics participants globally. It promises to make the writing process smoother, improve learning, and give personalized feedback. Yet, alongside the benefits, the technology has provoked another possibility regarding its misuse and the overuse on academic integrity. Therefore, this study aimed to explore the possible uses/ benefits and missuses/ threat of the use of AI-powered writing tools (ChatGPT & Quillbot) from students’ point of view. This study applied a qualitative study by menas of phenomenological approach. The participants were 8 students from 4 universities who have used those applications for their academic writing projects. Semi-structured interviews related to ChatGPT and Quilbot emphasis were conducted for the collection of data. The collected data identified through the interviews were analyzed through thematic analysis. The study found that participants use AI-Powered tools as feedback provider, writing assistant and problem solver for the deadlock. Nonetheless, they also revealed that the use of this AI tools could lead them to dependency, plagiarism and reduction of their crititical thinking and writing skills.